STRATEGI PEMASARAN TERHADAP KENAIKAN HARGA BAHAN POKOK SERTA MINAT BELI MENJELANG BULAN RAMADHAN DI PASAR INDUK CIBITUNG BEKASI - Taufik Ramdhani; Senny Amelia Dwiyanti; Tri Mulyani Kartini (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2025)
Ahead of Ramadan, the phenomenon of rising staple food prices in the market has become a recurring pattern and almost always happens every year. This condition affects people's purchasing power. The purpose of this study is to find out why the price of basic necessities in the market ahead of Ramadan always experiences an increase in market prices. As we know, the increase ahead of Ramadan and Eid al-Fitr is not a new song, but has become a habit. Based on this problem, the purpose of this study is to identify the factors that cause the increase in the price of basic necessities in the Bekasi Main Market. This study uses a qualitative method, with data sources from reference journals and direct interviews with business actors in the market. Some of the factors causing price increases include high demand that is not balanced with the availability of goods, raw material factors, production processes, distribution, and government policies.